Photodynamic Therapy as an Alternative Therapeutic Tool in Functionally Inoperable Oral and Oropharyngeal Carcinoma: A Single Tertiary Center Retrospective Cohort Analysis - Lambert, Arnaud; Nees, Lotte; Nuyts, Sandra; Clement, Paul; Meulemans, Jeroen; Delaere, Pierre; Vander Poorten, Vincent (Frontiers in Oncology, 2021)
Background: Head and neck cancer is typically treated with surgery, radiotherapy, chemoradiation, or a combination of these treatments. This study aims to retrospectively analyse oncological outcomes, adverse events and toxicity of treatment with temoporfin-mediated photodynamic therapy at a single tertiary referral center. More specifically, in a selected group of patients with otherwise (functionally) inoperable oral or oropharyngeal head and neck squamous cell carcinoma. Methods: 26 consecutive patients who received photodynamic therapy for oral or oropharyngeal squamous cell carcinoma from January 2002 until July 2019 at the University Hospitals Leuven were included. These were (1) patients with an accessible recurrent or new primary tumor in an extensively treated area of the head and neck, not suitable for standard treatment, or (2) patients that were judged medically unfit to undergo standard treatment modalities. Results: Complete tumor response was obtained in 76.9% of cases. Local control was obtained in 42.3% with a median recurrence free interval time of 9 months. Recurrence-free rates at six months, one year and two years are 60.6%, 48.5% and 32.3%. Recurrence-free interval was statistically more favorable for oropharyngeal squamous cell carcinoma (with or without oral cavity extension) in comparison to oral cavity squamous cell carcinoma alone (p<0.001). During a median follow-up period of 27 months, we report new tumor activity in 80.8% of patients. Median overall and disease-specific survival time was 31 and 34 months, respectively. Most reported adverse events were pain after treatment and facial edema. At the end of follow-up, swallowing and upper airway functionality were preserved in 76.9% and 95.7% of patients respectively. Conclusion: Photodynamic therapy is a valuable treatment option in highly selected patients with oral and/or oropharyngeal (functionally) inoperable head and neck squamous cell carcinoma. Treatment with this alternative modality can induce durable local control in an important fraction of treated patients, with an acceptable toxicity profile.